Development and Characterization of Norite-Based Cementitious Binder from an Ilmenite Mine Waste Stream - Mahmoud Khalifeh; Arild Saasen; Helge B. Larsen; Helge Hodne (Advances in Materials Science and Engineering)
Norite is a major type of solid waste generated during the production of ilmenite. This study focuses on the usability of norite as a solid precursor of alkali-activated cement. Sensitivity analysis was performed to find the influence of different alkali types and particle sizes of the source material on polycondensation. Norite was ground and mixed with sodium hydroxide and potassium hydroxide solutions to produce a binder. Potassium-containing systems were more effective compared to sodium-containing systems with respect to strength development. The X-ray diffraction patterns indicated formation of zeolites, albite, and oligoclase based on the type of activator and used additives. The patterns also revealed formation of an amorphous phase in the matrices of the binder that was cured at 87°C. Microstructure analysis revealed some degree of crystallization with different Si : Al ratios, which indicated heterogeneity of the binder matrices.